Guilt-based filmmaking: moral failings, muddled activism, and the "dogumentary" Get a Life. Issue 2 (2nd April 2018) - Hjort, Mette
ABSTRACT: To date consideration of negative emotions in the context of cinema has been largely limited to the issue of why spectators would be drawn to films that target psychological responses such as fear and disgust. The aim here is to consider the phenomenon of negative emotion as a motivating factor in the context of, not spectatorship, but film production. The focus is on documentary filmmaking with a strong ethnographic dimension, the camera being used to record the circumstances and culture of an ethnic group to which the filmmaker does not belong. Get a Life by Michael Klint (in collaboration with Claus Bie) is presented as an instance of guilt-based filmmaking, the filmmaker having repeatedly foregrounded his own guilt as a decisive factor in the film's making. A so-called "dogumentary" film based on filmmaker Lars von Trier's "Documentarist Code, " Get a Life is shown to rely on moral notions that are consistent with the future-oriented and redemptive aspects of the phenomenon of guilt. The filmmaker's rhetoric foregrounds the idea of "making a difference" for the Nigerian victims of a devastating flesh-eating disease (noma) and further purports to challenge the norms underwriting TV reporting on the "Third World." Analysis of Get a Life, however, reveals it to be a failed work on moral grounds. The filmmakers' self-importance, deficient self-understandings, and self-deceptions regarding the bases for their putative actions on behalf of others are identified as especially problematic. The relevant failings warrant attention at a time when filmmakers from privileged cultures increasingly pursue performative-style documentary filmmaking, fueled by purportedly moral intentions, in a variety of contexts in the Global South.